2018
DOI: 10.1055/a-0765-9078
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600E and Retinoic Acid in Radioiodine-Refractory Papillary Thyroid Cancer

Abstract: Radioiodine refractoriness in differentiated thyroid cancer remains an unsolved therapeutic problem. Response to retinoids might depend on specific genetic markers. In this retrospective analysis, associations between BRAF V600E and clinical outcomes after redifferentiation with retinoic acid (RA) and radioiodine therapy (RIT) were investigated. Thirteen patients with radioiodine-refractory (RAI-R) papillary thyroid cancer (PTC) were treated with 13-cis-RA followed by iodine-131 treatment at the Department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Retinoic acid is the bioactive metabolite of Vitamin A, which is a compound that potentially prevents or treats malignancy and which participates in multiple biological processes [29,30]. Retinoic acid can suppress the growth of cancer cells in vitro and induces cell death in breast cancer, neuroblastoma, gastric carcinoma, prostate cancer, pancreatic cancer, and acute promyelocytic leukemia cells [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid is the bioactive metabolite of Vitamin A, which is a compound that potentially prevents or treats malignancy and which participates in multiple biological processes [29,30]. Retinoic acid can suppress the growth of cancer cells in vitro and induces cell death in breast cancer, neuroblastoma, gastric carcinoma, prostate cancer, pancreatic cancer, and acute promyelocytic leukemia cells [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…At the clinical levels, the results of studies assessing the impact of vitamin A supplementation on human subjects with thyroid disorders have been controversial yet mostly promising. Recently, the use of vitamin A derivatives as a potential therapeutic option in thyroid cancer has gained the interest of researchers like never before (38,183,184). At this moment, we might have effective techniques to tackle some problems in this area.…”
Section: Recent Clinical Studiesmentioning
confidence: 99%
“…These authors also suggested that adequate vitamin A intake might be able to prevent extra-thyroidal extension and lymph node metastasis ( 52 ). Notably, one small group of patients with radioiodine-refractory thyroid cancer was treated with 13-cis-retinoic acid followed by iodine-131 treatment; after this “re-differentiation therapy,” 2 out of 3 patients whose cancers featured the BRAF V600E mutation showed a response expressed in terms of tumor size, serum Tg levels, and iodine uptake ( 53 ). Unfortunately, despite the interesting scientific basis, no studies have shown a definitive usefulness of vitamin A in thyroid cancer.…”
Section: Vitamin a And Thyroid Cancermentioning
confidence: 99%